Experimental Study of The Effect of Fluid Mass Flow on Cavitation of The Ebara 65x50 FSS4JA Type Centrifugal Pump in a TCU Casting Machine: CENTRIFUGAL PUMP - Safi'i, Muhamad; Nugroho, Agung; Ramdhani, Ahmad; Fahmi, Muhamad Idrokul; Nurkhalis, Yahdi Eka (CATHA SAINTIFICA, 2025)
Pumps are often found and needed in everyday life, both in households and industry. Cavitation is often a major problem in centrifugal pumps because it affects their performance and performance. Experimental studies on the effect of fluid mass flow rate on cavitation in centrifugal pumps were investigated and characterized. The Ebara Brand centrifugal pump type 65x50 FSS4JA installed in the Casting Machine TCU installation was used as the object of research. In the experimental study, the number of constant impeller blades of 6 pcs and a blade tilt angle of 60º was studied for variations in fluid mass flow rate determined with values ​​of 1.67 kg/s, 3.33 kg/s, 5.67 kg/s, and 7.33 kg/s. The results of the research show that the fluid mass flow rate has a cavitation value of 0.2 for variations in the fluid mass flow rate of 1.67 kg/s, 0.65 for variations in the fluid mass flow rate of 3.33 kg/s, 1.9 for variations in the flow rate fluid mass 5.67 kg/s, and 1.88 with variations in fluid mass flow rate of 7.33 kg/s. These results confirm that the higher the variation in fluid mass flow rate, the higher the cavitation level, but strangely when the variation is increased from 5.67 kg/s to 7.33 kg/s the cavitation value slowly decreases, this confirms that the variation in fluid mass flow rate 7.33 kg/s is the optimal fluid mass flow rate variation and allows it to be applied in the field.